The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/age.13040
|View full text |Cite
|
Sign up to set email alerts
|

Roan, ticked and clear coat patterns in the canine are associated with three haplotypes near usherin on CFA38

Abstract: Summary White coat patterning is a feature of many dog breeds and is known to be coded primarily by the gene micropthalmia‐associated transcription factor (MITF). This patterning in the coat can be modified by other factors to produce the attractive phenotypes termed ‘ticked’ and ‘roan’ that describe the presence of flecks of color that vary in distribution and intensity within otherwise ‘clear’ white markings. The appearance of the pigment in the white patterning caused by ticking and roaning intensifies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Whereas these haplotypes effectively differentiate clear from ticked dogs, no markers were identified that correlated with ticking density. Brancalion et al (2021) recognise that other haplotypes for the ticked phenotype also exist across the USH2A region. The functional mechanisms by which USH2A variants influence canine coat colour phenotypes have not yet been described.…”
Section: Ticking (T) and Roan (R)mentioning
confidence: 92%
See 4 more Smart Citations
“…Whereas these haplotypes effectively differentiate clear from ticked dogs, no markers were identified that correlated with ticking density. Brancalion et al (2021) recognise that other haplotypes for the ticked phenotype also exist across the USH2A region. The functional mechanisms by which USH2A variants influence canine coat colour phenotypes have not yet been described.…”
Section: Ticking (T) and Roan (R)mentioning
confidence: 92%
“…White markings are common across a range of canine coat colour phenotypes and can be highly variable, ranging from small flecks of white fur to fully or almost fully depigmented coats (Brancalion et al 2021). Blue eyes, occurring owing to a lack of melanin in the irides, are also commonly associated with such phenotypes (Caduff et al 2017).…”
Section: White Markingsmentioning
confidence: 99%
See 3 more Smart Citations